Rare Presentation of Primary Extramedullary Plasmacytoma as Lip Lesion - Mali Him; Maggie Meier; Vikas Mehta (Case Reports in Oncological Medicine)
Malignant plasma cell proliferation can be presented as part of disseminated disease of multiple myeloma, as solitary plasmacytoma of bone, or in soft tissue as extramedullary plasmacytoma. Extramedullary plasmacytomas represented approximately 3% of all plasma cell proliferation. Approximately 80% of extramedullary plasmacytomas occur in the head and neck region while the other 4% occur in the skin and to a lesser extent in the lip. In this paper, we report a rare case of primary cutaneous plasmacytoma involving the lip in a 65-year-old male. The patient presented with a nonhealing lower lip sore for the past 3 years. Upon further workup, there was no evidence of multiple myeloma or light chain disease. The patient was treated with radiation therapy and his last follow-up revealed no evidence of multiple myeloma or light chain disease.